Participatory modeling to assess the impacts of climate change in a Mediterranean vineyard watershed. (April 2022) - Naulleau, Audrey; Gary, Christian; Prévot, Laurent; Berteloot, Victor; Fabre, Jean-Christophe; Crevoisier, David; Gaudin, Rémi; Hossard, Laure
Abstract: The diversity of both pedoclimatic and socio-economic contexts in agricultural landscapes makes evaluating the impacts of climate change a challenge. Models are pertinent tools to quantitatively explore possible futures, and participatory approaches help account for local diversity. We developed a model through an approach that involves stakeholders in the model's construction and testing and in the discussion of results. We simulated spatially explicit impacts of climate change on water balance, grape phenology, and yield in a Mediterranean vineyard watershed for two climate scenarios. Results show a decrease in grape production of 7–14% by 2100. Yield decrease would be higher in irrigated high-yield areas despite a doubling of irrigation water supply. A forecasted 6 °C increase in temperature during berry ripening would threaten wine quality. The approach allows the communication of model results and limitations to stakeholders. It is a promising means of identifying potential local adaptations to climate change. Highlights: Participation allowed model design tailored to stakeholders' concerns. A new grape yield model (GraY) resulted from the participatory modeling approach. Without adaptation grape production would decrease from 5 to 16% by 2100. Irrigation water needs would double by the end of the century.